Accumulation of Aluminium and Physiological Status of Tree Foliage in the Vicinity of a Large Aluminium Smelter - E. D. Wannaz (The Scientific World Journal, 2012)
A pollution gradient was observed in tree foliage sampled in the vicinity of a large aluminium production facility in Patagonia (Argentina). Leaves of Eucalyptus rostrata, and Populus hybridus and different needle ages of Pinus spec. were collected and concentrations of aluminium (Al) and sulphur (S) as well as physiological parameters (chlorophyll and lipid oxidation products) were analyzed. Al and S concentrations indicate a steep pollution gradient in the study showing a relationship with the physiological parameters in particular membrane lipid oxidation products. The present study confirms that aluminium smelting results in high Al and sulphur deposition in the study area, and therefore further studies should be carried out taking into account potentially adverse effects of these compounds on human and ecosystem health.